P‐124: Perovskite Quantum Dots Display: Challenges and Opportunities. Issue 1 (29th May 2019) - Sinatra, Lutfan; Lutfullin, Marat; Mozo, Sergio Lentijo; Pan, Jun; Bakr, Osman M.
Abstract : Current results on the development of perovskite quantum dots for LCD displays are presented. It includes optimizing the synthesis, ligands engineering and shelling strategies to improve the quantum dots stability. Using these strategies, we are able to demonstrate the prototype of QDs polymer film for LCD backlighting that is stable during accelerated stability tests.